2005
DOI: 10.1029/2004ja010934
|View full text |Cite
|
Sign up to set email alerts
|

Toward magnetic field dissipation during the 23 July 2002 solar flare measured with Solar and Heliospheric Observatory/Michelson Doppler Imager (SOHO/MDI) and Reuven Ramaty High Energy Solar Spectroscopic Imager (RHESSI)

Abstract: [1] We analyze the SOHO/MDI high-cadence magnetic field variations that occurred in a bipolar area around the apparent neutral line (ANL) prior to and during the 2B/X4.8 flare on 23 July 2002 and their association with the hard X-ray (HXR) and H a emission observed with RHESSI and BBSO. Magnetic field changes started 6 min prior to the hard X-ray emission onset in 0.3-2 MeV band or 7 min in the 12-25 keV band and finished 20 min later. Before the flare, there are nine preexisting sources of a strong magnetic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 45 publications
(88 reference statements)
0
9
0
Order By: Relevance
“…Indeed, the results of our preliminary analysis suggest that abrupt and permanent magnetic changes are more prevalent in the ribbons, although the picture is still quite complex, perhaps due to the continuing flux emergence in the region. Further analysis making use of known methods (Sudol and Harvey, 2005;Zharkova, Zharkov, Ipson et al, 2005) and now available HMI vector magnetic data is needed to understand the variability of magnetic-field changes in seismic sources and this flare in general.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the results of our preliminary analysis suggest that abrupt and permanent magnetic changes are more prevalent in the ribbons, although the picture is still quite complex, perhaps due to the continuing flux emergence in the region. Further analysis making use of known methods (Sudol and Harvey, 2005;Zharkova, Zharkov, Ipson et al, 2005) and now available HMI vector magnetic data is needed to understand the variability of magnetic-field changes in seismic sources and this flare in general.…”
Section: Discussionmentioning
confidence: 99%
“…Later, when high-cadence longitudinal (line-of-sight) photospheric magnetic field measurements became available from NASA's Michelson Doppler Imager (MDI) onboard the Solar and Heliospheric Observatory (SoHO) satellite and the National Solar Observatory's Global Oscillations Network Group (GONG) ground-based network, the evidence for flare-related magnetic changes in the photosphere became clearer. Based on 1-min MDI longitudinal data, Zharkova (1999, 2001) reported sudden and permanent decreases in magnetic flux near X-class flares near magnetic neutral lines, and Zharkova et al (2005) found a permanent and significant increase in magnetic flux near the neutral line of a region during another X-class flare observed near the limb. Using 1-min GONG longitudinal magnetograms, Sudol and Harvey (2005) characterized the spatial distribution, strength, and rate of change of permanent field changes associated with 15 X-class flares by tracing the field changes pixel by pixel.…”
Section: Introductionmentioning
confidence: 96%
“…In consequence, plasma can escape from the corona and it was reported by Thompson et al (2000) that extended intensity depletions seen in EUV light during representative events mapped out the apparent footprints of CMEs contemporaneously observed in white-light coronagraph data. Also it was demonstrated (Zarro et al, 1999) that the possible explanation that coronal dimming is due to a local cooling effect (see, e.g., Chertok and Grechnev, 2003) is not supported by the observations since dimmings were simultaneously recorded within the same spatial location at different wavelengths (Attrill et al, 2008 and references therein). Spectral data confirm that dimming is due to mass loss Sterling, 2001, 2003;Harra et al, 2007).…”
Section: Coronal Mass Ejections and Coronal Dimmingmentioning
confidence: 95%
“…It was later argued by Zhang et al (2002) that loss of equilibrium within a magnetic coronal structure may trigger both a CME and a flare. Thereafter, Andrews (2003) demonstrated that only 60% of flares of M-class and higher are associated with CMEs.…”
Section: The Initiation Of Cmes and Flaresmentioning
confidence: 98%